Pemanfaatan Smartphone Sebagai Sarana Promosi Batik Incung, Jambi - Herlina, Vivi; Zam, Efvy Zamidra (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
Batik incung is a typical batik from Kota Sungai Penuh in Provinsi Jambi. The marketing method used is still conventional, by displaying products in stores. The workshop activities are carried out by using a smartphone as a tool because it is easier to use. The method is used not only in lectures, and discussions, but also in practical implementation. Three practices were given, promotion through social media, online store in the marketplace, and making promotional videos. The benefits that could be obtained not only increased knowledge and understanding about product promotion on the internet by using a smartphone, and being able to apply it. Therefore, this activity is expected can be applied continuously.